Enhancing the pregnant women knowledge through health education about high risk pregnancy - Zakiyya, Affi; Rusmini, Rusmini; Sartika, Qona Lutfi (Poltekkes Kemenkes Yogyakarta, 2019)
The cause of maternal death globally is still dominated by hemorrhage (27%), companion diseases (28%), and hypertension during pregnancy especially eclampsia (14%). Maternal mortality rates can be reduced by increasing awareness through health education during pregnancy and rapid decision making by recognizing the danger signs of a high-risk pregnancy. This study's purpose was to analyze the influence of health education to increase the knowledge of pregnant women about a high-risk pregnancy. This study was a quasi-experimental research with a pretest-postest design. The sample was taken using a purposive sampling technique with 60 respondents who met the inclusion criteria. Data was taken in 2017 in Cilongok II Public Health Center, Banyumas. The Instrument of this study was a questionnaire about a high-risk pregnancy and the intervention providing health education given by booklets. The data were analyzed using the Wilcoxon test. This study was showing that most respondent’s awareness of high-risk pregnancy before given health education was in the decent category (55%), after being given health education to increase to good knowledge (65 %). There was a difference in the level of knowledge before and after the health education was given (p-value=0.000). There was an increase in maternal knowledge about high-risk pregnancy after being given health education.